A continuidade e a ruptura. A evolução conceptual e a prática urbanística - Bruno Martin Amorim (2012)
By considering social frame contemporary issues (like global phenomenon orworld growth) - at a general scope - the main goal of our study is to inquire aboutrelevant features able to constitute actual urban realm. Given that built environmentrepresents society itself, the developed analysis seeks to figure out applicable urbanstrategies in order to enrich space and Man interactions.Cities, themselves, they tell stories of overlapped Times and they attract us by itsinherent 'space-time' environment trip. Thus, based on Joshep Rykwert work - TheSeduction of Place, History and Future of the City - we evaluate cities urban realm fromnineteenth century until nowadays, so that, we can demonstrate that the differentproposals are indeed resultant of rupture or continuity strategies.Rupture and Continuity concepts are seen as elementary basis of urban practice.Both are intervention criteria and, once identified, they are able to illustrate thecorrespondence between a particular urban model and main social representations(inherent to it).